ENTREPRENEURSHIP AS SIDE ACTIVITY (CASE STUDY ON FEMALE WORKERS AND FEMALE STUDENTS IN MANADO CITY) - Rarumangkay, Owen .; Massie, James .; Rumokoy, Farlane . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: The purpose of this research is to explore reasons and methods of female entrepreneur in Manado who conduct entrepreneurship as side activity. Especially with the current situation of the Indonesian workplace is being dominated by male, and there are already cases where female student succeed in having business while being an active. The type of this research is descriptive with qualitative approach and used triangulation methods as it tools. The methods used by the informants not so much different compared to those who conduct full-time entrepreneurship. With the informants aware of their entrepreneurial activity and has been planning ahead their entrepreneurship activity, to finally start it with their own personal saving as an initial capital. For the time management on both of their activity, most of them aware of their main activity’s responsibility and prioritize their main activity with less time allocated in their side activity. The result of reasons behind entrepreneurship activity are ‘hobby’, ‘for extra income’, ‘to be their own boss’, and ‘availability of own resources’. For female workers and students who have business idea or want to make extra money, conducting entrepreneurship might be a right choice, even if you have to start as side activity. Keywords: entrepreneurship, side activity, female entrepreneur, student entrepreneur.